Intracellular signaling in ER stress‐induced autophagy in skeletal muscle cells. Issue 5 (6th February 2013) - Madaro, Luca; Marrocco, Valeria; Carnio, Silvia; Sandri, Marco; Bouché, Marina
Abstract : Skeletal muscle remodeling in response to muscle disuse and unloading is known to be associated with so‐called ER stress, which, in turn, activates autophagy and contributes to muscle atrophy. Different molecules are involved in ER stress‐induced autophagy, among which PKCθ has recently been described. In this study, we dissected both in vitro and in vivo ER stress‐induced autophagy pathways in muscle. Using C2 C12 muscle cells in culture, we demonstrated that PKC activation induced autophagy in the absence of ER stress. We further demonstrated that PKCθ was strongly activated in cultured myoblasts and myotubes during ER stress induced by different stimuli, such as TG or TN treatment, and that it localized into Lc3‐positive autophagic dots upon TG treatment. Neither Akt dephosphorylation nor Foxo or GSK3β activation was observed in these conditions. Moreover, PKCθ inhibition in myoblasts and myotubes prevented ER stress‐induced Lc3 activation and autophagic dot formation, but not ER stress. In vivo, lack of PKCθ prevented both food deprivation‐ and immobilization‐induced autophagy and muscle atrophy, irrespective of Akt pathway inhibition. Taken together, these results demonstrate that PKCθ functions as an ER stress sensor in skeletal muscle, required for ER‐stress‐dependent autophagy activation, and can be proposed as a novel molecular target to maintain muscle homeostasis in response to external stimuli, such as disuse and unloading, still allowing intracellular clearance.—Madaro, L., Marrocco, V., Carnio, S., Sandri, M., Bouché, M. Intracellular signaling in ER stress‐induced autophagy in skeletal muscle cells. FASEB J. 27, 1990–2000 (2013). www.fasebj.org